(untitled) (Research, Society and Development, 2021)
The objective was to evaluate urban and environmental aspects, analyzing the perception of society in the Parque Zoológico de Goiânia in 2018. The methodology was divided into object, type of classification and stages of the research: a) evolution and occupation of urban land; b) characterization of the zoo by the geoprocessing instrument; c) society’s perception of the Zoological Park. Photographic records, Zoological Park projects, geoprocessing of Google Earth Pro satellite images, on-line Digital Basic Urban Map of Goiânia, Qgis and Google Earth software were used, and a questionnaire was applied to the population to analyze environmental variables. The results showed that since its creation, the zoo has received improvements to improve the animal enclosures and food, as well as reforestation. The location is easy to access, but suffers pressure from the occupation of buildings in its surroundings. Among the suggested proposals, we highlight having a park with only animals from the Cerrado or Safari model in Goiânia.